Implementation of Global NCD Monitoring Framework in Punjab, Haryana and Chandigarh–A Feasibility study - Bhattacharya, Sudip; Thakur, Jarnail Singh (Indian Journal of Community Health, 2017)
Background: In India, a national NCD monitoring framework was developed (June 2013) in consonance with the World Health Organization (WHO) global NCD monitoring framework with 10 targets and 21 indicators. A feasibility study was undertaken in Punjab, Haryana, and Chandigarh with few objectives. Objectives: To review the existing monitoring framework, identify the possible data sources, and collect the secondary data for NCDs. Methods: In-depth interview was conducted with the three state program officers (SPOs), and Health Management Information System (HMIS) reports (2010) were reviewed. Data from non-health sectors were collected and possible data sources were identified. Results: It was observed that SPOs were not clear of the data for indicators and targets. Food and drug licensing authority, schools, colleges, and offices may be possible sources of additional data. Current HMIS was inadequate. Multiple issues such as scarcity of data, excess dependency on hospital-based data, lack of manpower, inter-sectoral coordination, and periodic STEP wise approach to surveillance (STEPS) surveys are the major barriers for implementation. Conclusion: We concluded that with the existing resources, it was not feasible to implement the NCD monitoring framework. Recommendations: National surveys should incorporate NCD indicators, and periodic STEPS survey at state level are necessary for indicator generation.